Preparation Runners over Barrier to 400 Meters in Annual Training - Satkulov Bekzod Mavlyanovich (International Journal on Integrated Education, 2022)
The article presents the results of pedagogical experiments on the distribution of training loads and the dynamics of results in annual training cycles of 400 meter hurdles runners, as well as the formation of a special level of physical fitness.